Pengaturan Kekerasan Berbasis Gender Online: Perspektif Ius Constitutum dan Ius Constituendum (The Legal Policy of Online Gender Based Violence Regulation: Ius Constitutum and Ius Constituendum Perspective) - Puteri Hikmawati (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
The Covid-19 pandemic requires most people to undertake activities at home using information technology. This condition has an impact on the increasing cases of online gender-based violence (OGBV) against children and women. The handling of OGBV cases using Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law) and/or Law No. 44 of 2008 on Pornography (Pornography Law) is inadequate. This article examines the regulations of OGBV in laws and its application in the criminal justice system and its future regulations in the 2019 Criminal Code Bill and the Bill on the Elimination of Sexual Violence (PKS Bill). This study is written using a qualitative normative juridical research method and expected to improve criminal law knowledge. Based on the results of the study, the legal politics of OGBV regulation in ITE Law and Pornography Law raises multiple interpretations in its implementation. Law enforcement officers use ITE Law and/or Pornography Law against OGBV, where the victim can be made a suspect. This creates legal uncertainty and injustice for victims. The PKS Bill, which contains various types of sexual violence, is a Priority Bill for 2021 but does not explicitly stipulate OGBV. Therefore, OGBV needs to be included as a type of sexual violence in the PKS Bill. The PKS Bill is considered the lex specialis of the Criminal Code. AbstrakPandemi Covid-19 mengharuskan sebagian besar masyarakat beraktivitas di rumah dengan menggunakan teknologi informasi, kondisi tersebut berdampak pada meningkatnya kasus kekerasan berbasis gender online (KBGO) terhadap anak dan perempuan. Penanganan kasus KBGO dengan menggunakan UU No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (UU ITE) dan/atau UU No. 44 Tahun 2008 tentang Pornografi belum memadai. Artikel ini mengkaji pengaturan KBGO dalam hukum positif dan penerapannya dalam sistem peradilan pidana serta pengaturannya di masa yang akan datang dalam RUU KUHP 2019 dan RUU PKS. Penulisan artikel dengan metode penelitian yuridis normatif yang bersifat kualitatif ini diharapkan dapat menambah khasanah ilmu pengetahuan hukum pidana. Berdasarkan hasil kajian, politik hukum pengaturan KBGO dalam UU ITE dan UU No. 44 Tahun 2008 menimbulkan multitafsir dalam penerapannya. Aparat penegak hukum menggunakan UU ITE dan/atau UU No. 44 Tahun 2008 terhadap KBGO, dimana korban dapat dijadikan tersangka. Hal ini menimbulkan ketidakpastian hukum dan ketidakadilan bagi korban. RUU tentang Penghapusan Kekerasan Seksual yang memuat berbagai jenis kekerasan seksual merupakan RUU Prioritas Tahun 2021, namun belum juga memuat KBGO secara eksplisit. Oleh karena itu, KBGO perlu dimasukkan sebagai jenis kekerasan seksual dalam RUU PKS. RUU PKS dianggap sebagai lex specialis dari KUHP.